التغذية الراجعة في تنمية مهارة الكتابة باللغة العربية بوصفها لغة ثانية - Raihan binti Mohd Bakeri (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This research aims at identifying types of feedback used by teachers in improving the writing skill of the students who are studying two Arabic language courses, which are Arabic for Academic Purposes (LQ 4000) and the Arabic for Occupational Purposes (LQ 4400). It also aims at investigating types of feedback they prefer and the aspects of writing for which feedback is focused. The research was conducted on 144 students from the Centre for Languages and Academic Development (CELPAD) at the International Islamic University of Malaysia (IIUM). This study is a descriptive quantitative which uses mean and standard deviation in analysis. The research questionnaire used was adapted from previous studies, where it is designed as a tool for measurement for this research. Reliability test revealed that the items exceed the benchmark of a high degree of stability as the value of overall reliability coefficient, Cronbach-Alpha = .865. It was found that the teachers prefer using direct feedback in correcting writing errors on both sides of the content and grammar. The study also found students prefer feedback with explanation where the teacher write down the correct answer with errors underlined and for writing, students prefer if teachers focus more on contents and grammar lessons.